Prototype Pemilihan Dan Penggabungan Sumber Daya Secara Adaptif - Ibnu Hafizh; Nurhalim Nurhalim (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
This research discusses about the design and laboratory experiments for a module of prototype of hybrid system with three dc sources connected parallelly such as solar panels, windmills and waterwheels. This module is an important part of saving electricity consumption by using solar panels, windmills and waterwheels. It will receive power input from 3 sources, namely waterwheels, solar panels and windmills. It is shown that the simulation process and laboratory experiments can be drawn from several conclusions that this module can work in accordance with the desired conditions which can save electricity usage. Various dc voltage sources can be combined by supporting of contactor relays. The size of the dc voltage affects the power consumption from the source. Based on the prototype, the system implemented can increase the electricity consumption without PLN electricity. Keywords: hybrid system, dc voltage, relay contactor.